The biological functions of nonsense-mediated mRNA decay in plants: RNA quality control and beyond. (27th February 2023) - Raxwal, Vivek K.; Riha, Karel
Abstract : Nonsense-mediated mRNA decay (NMD) is an evolutionarily conserved quality control pathway that inhibits the expression of transcripts containing premature termination codon. Transcriptome and phenotypic studies across a range of organisms indicate roles of NMD beyond RNA quality control and imply its involvement in regulating gene expression in a wide range of physiological processes. Studies in moss Physcomitrella patens and Arabidopsis thaliana have shown that NMD is also important in plants where it contributes to the regulation of pathogen defence, hormonal signalling, circadian clock, reproduction and gene evolution. Here, we provide up to date overview of the biological functions of NMD in plants. In addition, we discuss several biological processes where NMD factors implement their function through NMD-independent mechanisms.